2008
DOI: 10.1038/sj.emboj.7601979
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin F is a cathepsin C-directed protease inhibitor regulated by proteolysis

Abstract: Cystatins are a family of naturally occurring cysteine protease inhibitors, yet the target proteases and biological processes they regulate are poorly understood. Cystatin F is expressed selectively in immune cells and is the only cystatin to be synthesised as an inactive disulphide-linked dimeric precursor. Here, we show that a major target of cystatin F in different immune cell types is the aminopeptidase cathepsin C, which regulates the activation of effector serine proteases in T cells, natural killer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(174 citation statements)
references
References 48 publications
8
154
0
2
Order By: Relevance
“…Cystatin F is made initially as an inactive disulphide-linked dimer [66][67][68]. Reduction generates an inhibitor able to target some endopeptidases but we found that carbohydrate-driven lysosomal targeting [69] resulted in monomerisation and activation by proteolysis, which extended the protease target range to enzymes such as cathepsin C [65]. The Eur.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Cystatin F is made initially as an inactive disulphide-linked dimer [66][67][68]. Reduction generates an inhibitor able to target some endopeptidases but we found that carbohydrate-driven lysosomal targeting [69] resulted in monomerisation and activation by proteolysis, which extended the protease target range to enzymes such as cathepsin C [65]. The Eur.…”
mentioning
confidence: 86%
“…Cathepsin C may itself be regulated by cystatin F. Cystatins are a family of proteinaceous cysteine protease inhibitors, some of which bind very tightly to cathepsin active sites [64]. We recently showed that cystatin F, which is principally found in immune cells, could inhibit cathepsin C [65]. Cystatin F is made initially as an inactive disulphide-linked dimer [66][67][68].…”
Section: Activation Of Granule Serine Proteasesmentioning
confidence: 99%
“…Because of these preprogrammed effector functions, several control mechanisms probably are needed to prevent potential damage to the fetus. These mechanisms could involve inhibitory natural killer receptors such as NKG2A and KLRG1, regulation of IFN-γ expression by TWIST1, and control of granzyme A activity by cystatin 7 (also known as "cystatin F") (46,52,79). In addition, in comparison with Vγ9Vδ2 T cells in adults, Vγ9Vδ2 T cells in early life appear to have a higher threshold for activation by phosphoantigens such as HMB-PP and IPP, especially for the production of cytokines (this study and refs.…”
Section: Discussionmentioning
confidence: 99%
“…Dimer to monomer conversion is facilitated by proteolytic cleavage at the N-terminus (78), probably by cathepsin V (41). Proteolytic processing changes its inhibitory profile and, while full-length cystatin F inhibits legumain and cathepsins F, H, K, L, S and V (77), the N-terminal processing is essential for cathepsin C inhibition (78). In addition, intracellular localization of the dimeric and monomeric forms is different: the dimeric form is found primarily in endoplasmic reticulum and Golgi apparatus, while the monomeric form is found in lysosomes and is completely truncated at the N-terminus (78).…”
Section: Cystatins and The Immune Responsementioning
confidence: 99%
“…Proteolytic processing changes its inhibitory profile and, while full-length cystatin F inhibits legumain and cathepsins F, H, K, L, S and V (77), the N-terminal processing is essential for cathepsin C inhibition (78). In addition, intracellular localization of the dimeric and monomeric forms is different: the dimeric form is found primarily in endoplasmic reticulum and Golgi apparatus, while the monomeric form is found in lysosomes and is completely truncated at the N-terminus (78). Furthermore, the secreted dimeric cystatin F can be internalized by other cells through the mannose-6-phosphate receptor pathway and can thus function also in trans (76).…”
Section: Cystatins and The Immune Responsementioning
confidence: 99%